Peran Pesantren dalam Melahirkan Kepemimpinan Muhammadiyah: Analisis Historis Terhadap Profil Ketua Umum Pimpinan Pusat Tahun 1912-2020 - Miswanto, Agus (Jurnal Tarbiyatuna, 2020)
This research is about the profile of Muhammadiyah leaders, who are the locomotive of modern Islamic organizations in Indonesia. This study tried to do a historical analysis of the profiles of Muhammadiyah leaders from three different periods, namely 1912-1952, 1953-1990, and 1990-2020. This study uses a historical approach with heuristic and interpretation methods. Through the heuristic method, data is collected, then grouped and finally interpreted using the inductive-synthesis method. From this research it was found that the Muhammadiyah leaders who were elected as the general chairmen of the Muhammadiyah central leadership were those who had a pesantren education base, both traditional and modern pesantren. From this research it is known, in the first period the role of traditional pesantren was very dominant in giving contribution to the leader of Muhammadyah, which was around 80%. Then, in subsequent developments, in the second and third periods, the dominance of traditional pesantren was displaced by modern pesantren (60%). Even so, traditional pesantren still contribute quite a lot in giving cadres to the Muhammadiyah central leadership, which is 40% each for the second and third periods